Turkey-Syria relations between enmity and amity - Hinnebusch, Raymond A.; Tur, Ozlem (Ashgate Pub., 2013)
In 1997 Turkey and Syria were on the brink of war, engaged in a very real power struggle. Turkey was aligned with Syria's main enemy, Israel, and there were seemingly intractable differences on the issues of borders, the sharing of river waters and trans-border communities. In less than a decade, relations were transformed from enmity to amity.